2004
DOI: 10.1046/j.1365-2842.2003.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Signs of temporomandibular disorders in tinnitus patients and in a population‐based group of volunteers: results of the Study of Health in Pomerania

Abstract: The literature has documented a controversial discussion on the possible relationship of otogenous symptoms and craniomandibular dysfunction since the 1920s. Therefore, an investigation was conducted which consisted of two parts: a case study with population-based controls and a cross-sectional study. The aim of the first study was to screen a group of patients suffering from acute or chronic tinnitus for temporomandibular disorders (TMD) in comparison with a population-based group of volunteers without tinnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 14 publications
3
83
1
13
Order By: Relevance
“…It is known that the pathophysiology of tinnitus remains unknown 35 and its relationship to TMD also is not clear. However, high frequency, moderate, oscillating, and sporadic intensities are usually is associated with TMD 12,36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the pathophysiology of tinnitus remains unknown 35 and its relationship to TMD also is not clear. However, high frequency, moderate, oscillating, and sporadic intensities are usually is associated with TMD 12,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is a fact that such symptom is more frequent among individuals with TMD than those in the general population [3][4][5][6][7][8][9] . Notwithstanding, in some studies which showed a greater prevalence of TMD signs and symptoms in tinnitus patients, they did not do any audiological evaluation or did not exclude those individuals with hearing loss from the sample and, therefore, did not rule out the otological etiology of the tinnitus 10,11 . Thus, the present study aimed at characterizing tinnitus in normal-hearing individuals and search for a possible relationship with Temporomandibular Dysfunction (TMD).…”
Section: Introductionmentioning
confidence: 99%
“…When more than 3 cm it is called an elongated styloid process causing dull pain in the ears, throat or mastoid region, difficulty in swallowing, foreign body sensation, symptoms of temperomandibular dysfunction like limited or asymmetric jaw movements or even carotid artery compression syndrome with rare cases of strokes [3][4][5][6][7][8]. Long styloid process was first described in 1652 by…”
Section: Introductionmentioning
confidence: 99%